Correction and modeling of position impact of current sensor of quantum direct current electricity meter - QIU Rujia; TIAN Teng; GENG Jiaqi; WANG Enhui; ZHAO Long; CHEN Yue (Diance yu yibiao, 2025)
To address the issue of increased error in current measurement by existing tunnel magnetoresistance (TMR) sensor arrays due to conductor eccentricity and tilt, as well as the challenge of accurate measurement with a large number of sensors, this paper proposes a current detection scheme using two tri-axial TMR magnetic sensors. We analyze the measurement principle for current within the circular range of two three-axis TMR magnetic sensors positioned on the circumference and derive the calculation formula. Experimental results demonstrate that the maximum relative error is 0.21% at 10% IMAX point. The relative error decreases rapidly with increasing current but remains unaffected by changes in conductor eccentricity and inclination, confirming that current measurement accuracy of this method is not influenced by these factors. In order to simulate real-world conditions more closely, we reduce the length of straight wire and bend both ends during experimentation, which introduces some errors due to the different conditions from the theoretical derivation. To correct these errors, we present a modeling method based on least squares quadratic and cubic fitting techniques. After fitting, the maximum relative error is reduced to 0.074%, with a coefficient of determination R2 equaling 1.000 0 and an MSE value of 1.18×10-4, achieving satisfactory results overall. In conclusion, utilizing double tri-axial TMR sensors along with our correction scheme effectively mitigates any impact from wire eccentricity, tilt, or bending on end-to-end current measurement errors while providing a way to enhance quantum DC electricity meter accuracy.